2023
DOI: 10.3390/pharmaceutics15061674
|View full text |Cite
|
Sign up to set email alerts
|

Pullulan/Poly(vinyl alcohol) Hydrogels Loaded with Calendula officinalis Extract: Design and In Vitro Evaluation for Wound Healing Applications

Abstract: The therapeutic efficiency of plant extracts has been limited by their poor pharmaceutical availability. Hydrogels have promising potential to be applied as wound dressings due to their high capacity to absorb exudates and their enhanced performance in loading and releasing plant extracts. In this work, pullulan/poly (vinyl alcohol) (P/PVA) hydrogels were first prepared using an eco-friendly method based on both a covalent and physical cross-linking approach. Then, the hydrogels were loaded with the hydroalcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 107 publications
1
6
0
Order By: Relevance
“…Moreover, due to the low diffusion in solid media, the hydrogels with high antimicrobial activity (high CO content) cannot prevent the growth of bacteria. Our results are comparable to previously reported studies [82,83].…”
Section: Antibacterial Assaysupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, due to the low diffusion in solid media, the hydrogels with high antimicrobial activity (high CO content) cannot prevent the growth of bacteria. Our results are comparable to previously reported studies [82,83].…”
Section: Antibacterial Assaysupporting
confidence: 93%
“…The in vitro release of CO from the hydrogels was carried out in PBS solution (pH 5.5) at 32 • C in order to simulate physiological dermal conditions by immersing 50 mg of the CO-loaded hydrogels in 4 mL of the release medium without stirring. At predetermined time intervals, 3 mL of the solution was withdrawn and the same volume of fresh buffer was added [57,82]. The amount of CO released was calculated from the UV absorbance peak at 280 nm using the same UV-vis spectrophotometer.…”
Section: In Vitro Clove Oil Release Studymentioning
confidence: 99%
“…Another important characteristic of a wound dressing is its biocompatibility. Several studies [ 97 , 98 , 103 , 106 , 108 , 109 , 110 ] demonstrated that HGs incorporated with PEs and EOs are biocompatible with minimal or no cytotoxicity. These formulations are also able to maintain fibroblast viability [ 101 , 104 , 106 ], while inducing their migration [ 97 , 109 , 110 ] and proliferation [ 101 , 104 , 106 ].…”
Section: Formulations Incorporated With Eos and Pesmentioning
confidence: 99%
“…It is worth it to mention that the ethanolic extracts decrease the consistency, firmness, and adhesiveness of the hydrogel [ 102 ]. Synthetic PVA hydrogels have also been tested by loading them with Calendula officinalis extract, which improves the adhesiveness and was effective against both Gram-positive and Gram-negative bacteria [ 103 ]. Curcumin, obtained from the roots of Curcuma longa, is a hydrophobic polyphenolic compound with remarkable bioactive properties, and promising results have been obtained by loading it into chitosan or PVA hydrogels [ 104 , 105 , 106 , 107 ].…”
Section: Classification Of Antimicrobial Hydrogelsmentioning
confidence: 99%